A dinâmica da inovação no Estado do Tocantins e a emergente necessidade de governança - Silva, Thays Lorrane da (Universidade Federal do Tocantins, 2020)
This article proposes a critical reflection on the state government's initiatives in promoting technological innovation of the Tocantins from the analysis of the data presented by the Ministry of science, technology and innovation - MCTI and Pintec search. The investigation evaluated the following areas related to C, T & I: human resources, resources applied, training grants, scientific production and patents. The search was developed in a qualitative way through the collect of data conduced bibliographic and documentary form. It is a study about the science of state action. The results of this investigation concluded that investments in C, T & I in the state are far below the necessary to make it a leading state, highlighting the effort insignificant that has been done to stimulate technological development in Tocantins.